The bcl-2 gene in primary B cell lymphoma of mucosa-associated lymphoid tissue (MALT). - Pan, L. (1989)
The bcl-2 gene rearrangement representing t(14:18) chromosomal translocation is the most frequent karyotypic abnormality in non-Hodgkin's lymphomas of follicle center-cell lineage. By using three bcl-2 DNA probes, 21 cases of non-Hodgkin's B cell lymphoma arising from gastrointestinal mucosa and eight cases of follicular lymphomas were examined. No rearrangement of the gene could be detected in the group of gastrointestinal lymphomas, although it was identified in 75% of the follicular lymphomas. The findings suggest that these two groups of lymphomas are not a family at genetic level and support the earlier suggestion that B cell lymphomas arising from gastrointestinal mucosa-associated lymphoid tissue are not of follicle center-cell lineage.